Students’ Perceptions Of Effective Teaching Characteristics In The College Of Education Studies, University Of Cape Coast, Ghana - Amakyi, Michael; Adu-Aboagye, Lily (Advances in Social Sciences Research Journal, 2016)
The study sought to investigate what students perceive to be effective teaching characteristics of lecturers in the College of Education Studies, University of Cape Coast, Ghana. A survey design was adopted to gather data from the study population (n=4,189) comprised of full-time undergraduate students of the five departments in the college. A multi-staged sampling utilising stratified, quota, and simple random sampling techniques was used to select a sample size of 495 students for the study. Data collected were analysed using means, standard deviations, and a one-way between-groups analysis of variance. The findings showed that the 39 teaching characteristics were perceived by the respondents as essential determinants of effective teaching characteristics.The respondents identified teacher preparation as the extremely important effective teaching characteristic. The study recommendations included conducting a similar study using both students and lecturers to ascertain if the instructor and the learner share similar perceptions with regard to effective teaching characteristics.